FORMATION OF SCIENTIFIC RESEARCH COMPETENCE OF MASTER'S DEGREE STUDENTS BY MEANS OF BYOD TECHNOLOGY - Shykyrynska, Oleksandra; Vyshkivska, Vanda; Remnova, Anzhelika; Malinka, Olena; Lobachuk, Inna; Kryvosheya, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The authors of the article analyzed the features of using the innovative BYOD (Bring Your Own Device) technology in the formation of research competence of master's degree students. The European experience of applying BYOD technology is analyzed. Emphasis is placed on the relevant use of this technology in higher education institutions, which is related to the digitalization of the educational process, the pandemic and martial law in Ukraine. The results of the ascertaining phase of the pedagogical experiment are presented, the participants of which were master's degree students of Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University and Mykhailo Drahomanov Ukrainian State University (Kyiv). The students are enrolled in such academic programs as “Pedagogy of Higher Education. Tutoring”, “Counseling”, “Preschool Education. Primary Education”, “Preschool Education. Speech Therapy”, “Physical Therapy, Occupational Therapy".The article reveals the educational potential of BYOD technology for the formation of scientific research competence of master's degree students. It is noted that the use of this technology in terms of offline, online and mixed studying helps higher education students acquire skills necessary to analyze, generalize, systematize and compare information. In addition, information retrieval and critical analysis skills are successfully formed. The differences in the application of this technology in conditions of individual and group work with master’s degree students are shown.